Climate Crises and Crypto-Colonialism: Conjuring Value on the Blockchain Frontiers of the Global South - Howson, Peter (Frontiers in Blockchain, 2020)
In this commentary we explore how international development, disaster relief and climate change mitigation credentials are being called upon to justify ‘crypto-colonialism’, whereby blockchain technology is used to extract economic benefits from those suffering the scars of colonial expansionism in the Global South. These benefits include land, labour and resources needed to facilitate local ‘crypto-utopian’ developments, or a ‘green economy’ elsewhere. As with past neoliberal development agendas imposing structural economic reforms, the contemporary crypto-colonial exercises discussed here are driven in pursuit of a common good – to protect the global commons and improve people’s lives. Within spaces where crypto-colonialism manifests, the governance frameworks of the associated technology is heavily entangled with social-spatial relations in multiple ways. We argue that despite being distributed, techno-ecological fixes are never placeless. How people engage with, resist or reconfigure a crypto-economy is geographically contingent. This commentary argues for more situated critical analysis of actually existing case-studies to reveal the inequitable terrain of project benefit distributions, and to expose the likely winners and losers within each. The success or failure of use-cases is less dependent on technical viability, but rather mediated through reactions to colonial contexts and historical experiences of various economic and climate crises.